Countering Radicalism through Inclusive Islamic Education: A Study of Raḥmatan lil ‘Ālamīn Values among University Students - Ahmad Syauqi Hidayatullah; Rochmad Novian Inderanata; Khotim Hanifudin Najib (KURAS Institute, 2025)
This study examines the role of inclusive Islamic education in countering radicalism among university students, focusing on their understanding of the Raḥmatan lil ‘Ālamīn (IRA) values. The IRA concept promotes compassion, tolerance, and dialogue. These values serve as a potential ideological counterweight to extremism. Using a quantitative survey method, data from 369 students were analysed through Pearson's correlation to examine the relationship between inclusive Islamic values and radical tendencies. The results revealed that the majority of students had internalised IRA values, demonstrating high levels of positive attitudes across all four domains. Pearson's correlation analysis revealed a significant negative correlation (p < 0.01) between IRA values and radical inclinations. This suggests that students who embrace moderate Islamic ethics are less vulnerable to extremist ideologies. Notably, tolerance and democratic values exhibited the strongest inverse relationships with fanatical and radical attitudes. These findings emphasise the importance of incorporating inclusive Islamic values into higher education curricula as a preventive measure against ideological radicalisation. By fostering environments that emphasise peace, pluralism, and civic responsibility, educational institutions can play a key role in promoting moderation and resilience against extremism among young people.